Drowsiness and mental exhaustion can be triggers of acceleration of the subjective time passag - Цибульський, Арман (Психологічний журнал, 2023)
This article is devoted to the study the prevalence of the experience of accelerated subjective time passage (ASTP) among the population in Ukraine in 2021 (N=74). Widespread prevalence has been found, 64,41 % of the respondents noticed the signs of the phenomenon. The origin of the experience on the basis of previous studies and analysis of the given data hypothesized. The correlation with age was analyzed. No significant correlations were found, but in the first age group (20-29 years old) there was an unnatural excess of the number of respondents who mentioned ASTP, which allowed us to assume the multi-causality of the phenomenon. The main idea put forward by the analysis of the data was the emergence of ASTP as a consequence of loss of consciousness quality. Correlations were found between the responses of participants noting ASTP and weakness, laziness, unwillingness to develop and muted consciousness (r=0.266; p=0.022). Further investigating of the relationships led to the assumption that main trigger for the occurrence of the phenomenon is drowsiness, which reduces the consciousness quality.